2018
DOI: 10.1111/gbb.12518
|View full text |Cite
|
Sign up to set email alerts
|

Role of social cognition in post‐traumatic stress disorder: A review and meta‐analysis

Abstract: Social functioning is a key component of recovery after a potentially traumatic experience, and the buffering role of the social support in trauma resilience and recovery has been very well documented. Factors contributing to resilience and recovery are notable because although most people will experience a traumatic event during their lifetimes, only 6% to 10% are diagnosed with post-traumatic stress disorder (PTSD). The relationship between an individual and their social environment is determined both by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 72 publications
(138 reference statements)
5
65
0
Order By: Relevance
“…The present review highlighted the difficulty of studying social cognition, owing to the heterogeneity of the data. A recent meta‐analysis conducted by Stevens and Jovanovic evidenced social cognitions deficits in PTSD patients (Stevens & Jovanovic, ). Author also noted the extreme heterogeneity of studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present review highlighted the difficulty of studying social cognition, owing to the heterogeneity of the data. A recent meta‐analysis conducted by Stevens and Jovanovic evidenced social cognitions deficits in PTSD patients (Stevens & Jovanovic, ). Author also noted the extreme heterogeneity of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the variability induced by type of trauma and sex, we believe that trauma involving another human being (i.e., interpersonal) further impairs social cognition. In Stevens and Jovanovic meta‐analysis (Stevens & Jovanovic, ), the effect size by type of trauma revealed that interpersonal trauma provoked more damages in social cognition than a natural disaster for instance. As they included childhood trauma in their analysis, complex PTSD patients may have biased result (atypical social cognition development, re‐victimization as it is evoked in their review).…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed a demographic questionnaire where they provided information about their age, gender, race/ethnicity, and highest level of educational achievement. All participants also completed the Medical Outcomes Survey brief Social Support questionnaire (MOS-SS; Sherbourne & Stewart, 1991) -a measure of perceived social support -which was included in the analysis as social support has previously been shown to play a vital role in resilience to psychopathology following trauma (Fritz et al, 2018;Stevens & Jovanovic, 2019). A subset of individuals (N=24) completed the Cogstate battery, a set of computerised tests probing general executive function that have been shown to be sensitive to mild cognitive impairment (Maruff et al, 2009).…”
Section: Demographic and Clinical Measuresmentioning
confidence: 99%
“…One further study found evidence that greater maternal support attenuated the relationship between childhood adversity and neural responses to fearful emotional faces in the anterior cingulate cortex, insula, nucleus accumbens, and frontal pole (Wymbs et al, 2020). Importantly, higher levels of social cognitive function (ability to infer the thoughts of others and navigate the social world) may help foster adaptive outcomes following trauma, by conferring the ability to recruit and maintain these important social support structures (Stevens and Jovanovic, 2019;Lepore and Kliewer, 2019). However, to date, very few studies have examined role of neural activity related to social cognition in resilience following trauma exposure.…”
Section: Social Support and Social Cognitionmentioning
confidence: 99%